Between Ordinary and Extraordinary: A Deweyan Approach to Ordinary, Aesthetic, and Cultic Experience - Dahl, Espen (Harvard theological review, 2020)
The relation between the everyday and the religious cult has traditionally been regarded as one of opposition, like the profane and the sacred. Since such a conception comes with a high price—rendering the cult esoteric and the everyday bereft of religious significance—this article proposes a more complex dynamic between the two. Drawing on Dewey’s idea of aesthetic experience as an intensification of ordinary experience, the article argues that a similar structure should be applied to the cult, or, more specifically, cultic play. In cultic play, there is admittedly discontinuity from ordinary life, owing to play’s distinct settings and rules. Nevertheless, such discontinuity reveals a deeper continuity, in which ordinary experience becomes present in new, sacred ways. In a dialectical manner, cultic play draws on ordinary experience, discloses and intensifies it through the context of play, and thus points forward to possibilities for inhabiting the everyday in richer ways.